The Dimensions of Poverty and its Effects on Nigerias National Development (Global Journal of Human-Social Science, 2022)
This paper examines the dimensions of poverty and how it affects national development in Nigeria. It therefore, views poverty as a phenomenon that affects the socio-economic and political conditions of its victims in both developed, developing and underdeveloped countries. Relying on qualitative data, this paper used the political economy approach to argue that the underdevelopment of the productive forces occasioned by politics of primitiveness orchestrated by the political class is largely the cause of the poverty in Nigeria. It is against this analytical angle that the paper reveals that poverty in Nigeria has resulted to inequality, social injustice, conflict, crime and consequently leading to political apathy and sometime vote buying during elections. With these dimensions, it concludes that the nature and character of poverty in the country pose challenges to Nigeria's national development. Because sustainable national development cannot be achieved in a poverty ridden nation hence, the menaces of poverty are recipes for anti-nation building culture.
Keywords: poverty; national development; dimensions; effects; challenges